Pituitary hyperplasia due to Himalayan endemic hypothyroidism. Issue 2 (2nd December 2020) - Sapkota, Shabal; Sapkota, Sulav; Karn, Mitesh
Abstract: Pituitary hyperplasia due to hypothyroidism can be treated medically. This condition should not be mistaken for adenoma and surgery should be avoided. Abstract : Pituitary hyperplasia due to hypothyroidism can be treated medically. This condition should not be mistaken for adenoma and surgery should be avoided.